Factors Associated with Tobacco Cessation in Primary Health Care - Melnick, Ricardo; Rech, Gabriela Soares; Rech, Rafaela Soares; Faustino-Silva, Daniel Demétrio (International Archives of Otorhinolaryngology, 2021)
Introduction Cigarettes are the main cause of preventable death in the world, and primary health care services can contribute to the management of this habit.Objective To describe and analyze the factors associated with tobacco cessation in groups of smokers in primary health care.Methods The present is a cross-sectional study conducted in 12 primary health care units from July 2016 to May 2017. We investigated sociodemographic and health variables, as well as smoking characteristics and different interventions for tobacco cessation, with the outcome being studied and analyzed after the fourth group care session.Results We evaluated 329 smokers, of which 182 quit smoking after the fourth interview. Most of the individuals who quit smoking were women (n = 121, 66.5%), with a monthly income of 2 to 5 minimum wages (n = 88, 77.9%). After the multivariable analysis, we observed that tobacco cessation was significantly associated with depression (prevalence ratio [PR] = 1.11; 95% confidence interval [95%CI] = 1.02 to 1.22), as well as with belonging to the groups which used as approaches motivational interviewing (PR = 1.21; 95%CI = 1.13 to 2.01), patches (PR = 1.36; 95%CI = 1.24 to 1.48), and bupropion (PR = 1.16; 95%CI = 1.03 to 1.31).Conclusion Primary health care is the ideal site for the reduction of smoking rates, given that different technologies may be applicable and useful for tobacco cessation. The comprehensiveness and longitudinal care offered in primary care may provide opportunities for health professionals to understand which is the best technology for each health system user, thus contributing to personalized care.
Keywords: smoking; tobacco; primary health care